The Adaptive Significance of Tail‐Flagging: A Test in European Rabbits (Oryctolagus cuniculus) - Yuqian Huang; Reuben Evan Sparke; Tim Caro (Ecology and Evolution, 2025)
ABSTRACT Mammals are typically characterised by dull brown or grey colouration for camouflage, yet a number of species exhibit striking white underparts, including the underside of the tail, which can be facultatively displayed when the tail is raised. Nonetheless, the adaptive significance of raising a white tail by mammals is poorly understood. To investigate this, we observed 2169 escape events from wild European rabbits (Oryctolagus cuniculus), using human approaches, taxidermy predator models (fox, marten) and live buzzard attacks and tested seven hypotheses, including alarm signalling, quality advertisement and confusion effect. We further conducted phylogenetic comparative methods across Lagomorphs to examine whether the evolution of white tails is associated with ecological and social traits. We found that tail‐flagging is complex, conveying rather different information at distinct stages of predator encounters. Before escape, exposing the underside of the white tail seems to be an alarm signal to warn conspecifics. During escape, however, there was some evidence that it could serve as a quality advertisement signal to deter predator pursuit. It is also possible that in high local density populations, tail‐flagging behaviour could confuse predators. We could categorically reject vigilance advertisement, perception advertisement and group cohesion as explanations for this behaviour. The study sheds light on the evolutionary significance of conspicuous undersides in mammals and highlights the surprising complexity of signalling behaviours in predator–prey interactions.